HEALTH EDUCATION ON FRACTURES EMERGENCIES TO INCREASE KNOWLEDGE AMONG SMK KESEHATAN LETRIS INDONESIA 1 STUDENTS - Sasmito, Priyo; innekerisnawati, Duwi; Hutasoid, Daud Letare; Rafi, Rafi; Aprila, Rizki; cindy, Aghestine Amara (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2023)
Fractures are fractures usually caused by trauma or physical exertion, accidents, both work accidents and traffic accidents Fractures are a potential or actual threat to a person's integrity, so they will experience physiological and psychological disorders that can cause a response in the form of pain. , Indonesia is the country that experiences the most fracture events 1.3 million per year from its population, which is around 238 million, and the most results are found at the age in the late adolescent category 17-25 (28.6%) because age is the productive age in carrying out activities, male sex (63.5%) the location of the Os fracture. Humerus (27.0%) location on bone 1\3 distal (50.8%) type of closed fracture (68.8%) and the cause of the fracture trauma (96.8%) However, the majority of adolescents do not understand well how to handle early fracture injuries. Incorrect initial handling can have an impact on complications for fracture sufferers Objective: This community service activity aims to increase the knowledge and understanding of adolescents in the early handling of fracture injuries Especially Students of SMK Kesehatan Letris Indonesia 1.